Length–weight relationships of nine fish species from the Tongjiang section of the Songhua River, China. (11th April 2017) - Huo, T. B.; Yuan, M. Y.; Wang, J. L.; Li, P. L.; Liu, W.; Wu, X. C.
Summary: Length–weight relationships were evaluated for nine fish species from the Tongjiang section of the Songhua River in China. A total of 675 fish specimens were collected from 4 May to 29 October 2014. Length–weight relationships for six fish species ( Romanogobio tenuicorpus, Leuciscus waleckii, Opsariichthys bidens, Microphysogobio amurensis, Pelteobagrus ussuriensis and Misgurnus mohoity) were new to FishBase in 2015, but the length–weight relationships of P .  ussuriensis was studied by Ma in 2015. New data on M. mohoity is offered, and this study also shows new maximum total lengths for three fish species. The r 2 values ranged from .95 to .99. Values of b varied from 2.504 to 3.471.